2021
DOI: 10.5114/wiitm.2021.103922
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic colonoscopy in colorectal cancer screening - a randomized controlled trial.

Abstract: Introduction: Colonoscopy is considered the gold standard for colorectal cancer screening. Panoramic colonoscopy offers better visualization to decrease the adenoma miss rate. Aim: To assess the influence of 330° panoramic view colonoscopy on adenoma and polyp detection rate, cecal intubation time, and examiner's comfort. Material and methods: The study enrolled 421 patients aged 18-80 years who were eligible for colonoscopy screening. Patients with prior abdominal surgery, inflammatory bowel disease or after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Colonoscopy is crucial to diagnosis and treatment of precancerous colonic lesions [20]. Proper bowel preparation is crucial to the efficacy of colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonoscopy is crucial to diagnosis and treatment of precancerous colonic lesions [20]. Proper bowel preparation is crucial to the efficacy of colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Colonoscopy is the gold standard for finding and removing precancerous colonic lesions [1]. Quality of bowel preparation is related to the rate of detection of polyps and adenomas [2,3]. However, it has been reported that approximately 30% of patients fail to achieve adequate bowel preparation in many countries and regions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%